Pregestational diabetes increases fetoplacental vascular resistance in rats - Vajnerova, Olga; Kafka, Petr; Kratzerova, Tereza; Chalupsky, Karel; Hampl, Vaclav (Placenta, 2018)
INTRODUCTION: Diabetes is a well-known risk factor in pregnancy. Because maternal diabetes involves oxidative stress that is also induced by chronic hypoxia and can alter vascular function, we sought to determine the effects of chronic maternal hyperglycemia on the fetoplacental vasculature in rats and to compare it with the effects of chronic hypoxia. METHODS: Diabetes was induced in female rats by a streptozotocin injection at a neonatal age. When these animals reached adulthood, their hyperglycemia was confirmed and they were inseminated. Half of them were exposed to hypoxia (10% O2) for the last week before the delivery. One day before the expected date of delivery, one of their placentae was isolated and perfused. RESULTS: Fetoplacental vascular resistance was increased equally by experimental diabetes, chronic hypoxia, and their combination. Fetoplacental perfusion pressure-flow analysis suggested increased resistance in the small vessels in chronic hypoxia and in larger vessels in diabetes. Fetal plasma nitrotyrosine levels, measured as a marker of peroxynitrite (reaction product of superoxide and nitric oxide), mirrored the differences in fetoplacental resistance, suggesting a causative role. Fetoplacental vasoconstrictor reactivity to acute hypoxic stimuli was reduced similarly in all groups. Fasudil, a strong vasodilator agent, reduced fetoplacental vascular resistance similarly in all groups, suggesting that for the observed differences among the groups, the changes in vascular morphology were more important than variances in vascular tone. DISCUSSION: Maternal diabetes increases fetoplacental vascular resistance to a similar extent as chronic hypoxia. These stimuli are not additive. Changes in vascular tone are not responsible for these effects.
Keywords: gestační diabetes; Rats; hypoxie; Hypoxia; těhotenství; Fetoplacental vessels; placenta; Oxidative Stress; Placenta; Placental Circulation; krysa rodu Rattus; Diabetes, Gestational; cévní rezistence; experimentální diabetes mellitus; ženské pohlaví; zvířata; Chronic hypoxia; Pregnancy; Diabetes Mellitus, Experimental; Diabetes; Vascular Resistance; oxidační stres; Female; placentární oběh; Oxidative stress; Animals